An Image Encryption Technique using Sine Curve - Das, Sujit Kumar; Dhara, Bibhas Chandra (2017 Ninth International Conference on Advances in Pattern Recognition (ICAPR), 2017)
In this article parametric curve based a new image encryption method is proposed. Here, to obtain the encrypted image, sine curves (sin(a, w, ¢, t) = a * sin(¢ + 27rwt)) have used in both confusion and diffusion phases. In different steps, different sine curves have used, with varying the parameters and this provide more security to the proposed method. The result of the proposed method, performance under different statistical analysis and sensitivity analysis established that proposed method provides a secure and efficient way for image encryption.